2016
DOI: 10.1007/s00128-016-1857-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Heavy Metal Pollution in Surface Soil Samples in China: A Graphical Review

Abstract: Soil pollution in China is one of most wide and severe in the world. Although environmental researchers are well aware of the acuteness of soil pollution in China, a precise and comprehensive mapping system of soil pollution has never been released. By compiling, integrating and processing nearly a decade of soil pollution data, we have created cornerstone maps that illustrate the distribution and concentration of cadmium, lead, zinc, arsenic, copper and chromium in surficial soil across the nation. These summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(71 citation statements)
references
References 13 publications
2
69
0
Order By: Relevance
“…Soils in China also suffer from high degrees of contamination. A report of the national survey of soil contamination of China, which was published in 2014, showed that the exceedance of environmental standards for Cd, Hg, As, Cu, Pb, Cr, Zn, and Ni in soil samples reached 7.0%, 1.6%, 2.7%, 2.1%, 1.5%, 1.1%, 0.9%, and 4.8%, respectively [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Soils in China also suffer from high degrees of contamination. A report of the national survey of soil contamination of China, which was published in 2014, showed that the exceedance of environmental standards for Cd, Hg, As, Cu, Pb, Cr, Zn, and Ni in soil samples reached 7.0%, 1.6%, 2.7%, 2.1%, 1.5%, 1.1%, 0.9%, and 4.8%, respectively [6]. …”
Section: Introductionmentioning
confidence: 99%
“…The application of urban composts, metal-based pesticides, ripening agents, and fertilizers and wastewater irrigation have resulted in increasing cadmium (Cd) accumulation in orchard soil of many parts of the world especially in developing countries (Andreu and Gimeno-García, 1996; Pinamonti et al, 1997; Li et al, 2014; Wang et al, 2015b; Duan et al, 2016). Cd contamination in orchard soil could inhibit net photosynthesis, decrease chlorophyll, repress plant growth, alter carbohydrate concentrations, limit fruit cultivation, and poses a threaten to human health (Hamurcu et al, 2010; López-Climent et al, 2011; Podazza et al, 2012; Stachowiak et al, 2015; Wang et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Soil from places like railway station is composed of many heavy metals that is a inhibiting factor for microorganism to survive. Generally, microorganisms end up in forming separate colonies in order to produce useful enzymes like lipases, proteases, amylases and cellulases [3,4]. This enzymatic production enable them to utilize virtually every organic compound present in their niche [5].…”
Section: Introductionmentioning
confidence: 99%